The Role of Zwitterionic Materials in the Fight against Proteins and Bacteria - Colilla, Montserrat (Medicines (Basel), 2018)
Zwitterionization of biomaterials has been heightened to a potent tool to develop biocompatible materials that are able to inhibit bacterial and non-specific proteins adhesion. This constitutes a major progress in the biomedical field. This manuscript overviews the main functionalization strategies that have been reported up to date to design and develop these advanced biomaterials. On this regard, the recent research efforts that were dedicated to provide their surface of zwitterionic nature are summarized by classifying biomaterials in two main groups. First, we centre on biomaterials in clinical use, concretely bioceramics, and metallic implants. Finally, we revise emerging nanostructured biomaterials, which are receiving growing attention due to their multifunctionality and versatility mainly in the local drug delivery and bone tissue regeneration scenarios.